2016
DOI: 10.1590/0101-416146128aaa
|View full text |Cite
|
Sign up to set email alerts
|

Custo de vida comparativo das regiões metropolitanas brasileiras: 1996-2014

Abstract: Resumo Neste trabalho estimamos os níveis de custo de vida de 11 regiões metropolitanas brasileiras no período 1996-2014. Aplicamos o método Country Product Dummy (CPD) a dados das pesquisas de orçamentos familiares de 1996, 2003 e 2009. Interpolamos os pesos orçamentários para os anos intermediários e usamos dados de índices de preços regionais para interpolar e atualizar os preços. Os resultados indicam que os maiores custos de vida estão em Brasília, São Paulo e Rio de Janeiro, sendo que Goiânia apresentou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 8 publications
0
21
0
12
Order By: Relevance
“…Góes and Matheson (2017) have documented large divergences of productspecific price dynamics, particularly for non-tradables, across different metropolitan areas. Almeida and Azzoni (2016) showed that overall price level differences in Brazilian metro areas can diverge with levels as low as -19 percent and as high as +14 percent from the national average.…”
Section: Box 1 the Cost Of Living Adjustmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Góes and Matheson (2017) have documented large divergences of productspecific price dynamics, particularly for non-tradables, across different metropolitan areas. Almeida and Azzoni (2016) showed that overall price level differences in Brazilian metro areas can diverge with levels as low as -19 percent and as high as +14 percent from the national average.…”
Section: Box 1 the Cost Of Living Adjustmentmentioning
confidence: 99%
“…Given that overall spatial price differences can be well approximated by a linear function of housing spatial price differences, we use the parameter from Azzoni and Almeida (2016), assumed to be homogenous across regions, and our heterogeneous rental spatial-price difference index to fit an overall spatial price difference index ̂, , = , ,…”
Section: Box 1 the Cost Of Living Adjustmentmentioning
confidence: 99%
“…Indeed, almost half of public sponsored pension funds are related to the federal government, which implies that most of the employees are located either in Brasilia (the capital of Brazil), or in Rio de Janeiro (the former capital of Brazil, that still concentrates some federal activities). These metropolitan regions, along with São Paulo, historically present the greatest costs of living in Brazil (Almeida & Azzoni, 2016). We evaluate the influence of location on total administrative expenses using dummies for location.…”
Section: Hypothesesmentioning
confidence: 99%
“…We use a dummy to identify headquarters located in São Paulo (SP), Rio de Janeiro (RJ) or Capital District (CD) because Almeida and Azzoni (2016) report that the main metropolitan areas of these states and district have the most expensive costs of living in Brazil. Although their analysis covers only the metropolitan areas, and our dummy is for states, most of the EFPCs' headquarters are located in metropolitan areas, especially for the Capital District and Rio de Janeiro.…”
Section: Cdorrjorspmentioning
confidence: 99%
“…Góes and Matheson (2017) have documented large divergences of product-specific price dynamics, particularly for non- tradables, across different metropolitan areas. Almeida and Azzoni (2016) showed that overall level price differences in Brazilian metro areas can diverge with levels as low as -19 percent and as high as +14 percent from the national average.…”
Section: Box 1 the Cost Of Living Adjustmentmentioning
confidence: 99%